Teaching and researching quality indicators: a partnership with middle school students - Sandra Lúcia Ferreira; Margaréte May Berkenbrock-Rosito; Julio Gomes Almeida (Ensaio, 2018)
Discussions about the quality of public education have generated concerns that are at the base of public policies such as SAEB – Sistema de Avaliação da Educação Básica [Elementary and Middle School Evaluation System], meant to work with quality standards defined by educators themselves. Some scholars accuse this system of having merely regulatory purposes. This study broadens the discussion by investigating students’ opinions on Educational Quality. Our aims are: to identify what 8th graders understand by educational quality; to investigate the prevailing educational quality concepts in school discourses; to discuss how students understand the notion of educational quality. The methodology articulates documental study and field work (questionnaire and focus groups). The collected data were analyzed with two text analysis software: Analyse Lexicale par Contexte d’un Ensemble de Segment de Texte (ALCEST) and Statistical Package for the Social Sciences (SPSS). The study involved 227 students from four different public schools (two city schools and two state schools) and members of the Education Master’s Program of a private university located in the city of São Paulo’s eastern area. The results highlight the importance of: a) participating in school dynamics and b) developing a good relationship between the students and other school members, as well as the need to: a) restore respect and trust between students and educators, b) have school activities that can make people feel valued and c) educate the teachers/researchers to encourage them to listen to their students.